Applied Computational Thinking with Python Design Algorithmic Solutions for Complex and Challenging Real-World Problems. - Jesús, Sofía De (Packt Publishing, Limited, 2020)
Applied Computational Thinking with Python provides a hands-on approach to implementation and associated methodologies that will have you up-and-running, and productive in no time. Developers working with Python will be able to put their knowledge to work with this practical guide using the computational thinking method for problem-solving.